Art and Homeopathy—A New Rubric - Hamilton, Ian (Homœopathic Links, 2015)
This is the first of what we hope will be a series of interesting contributions about the relationship between art and homeopathy and the art and science of homeopathy. Many have noted this connection between art and homeopathy, and there is something about the nature of the creative force and the way in which we perceive the vital force as creative, which puts homeopathy in the same dynamic place as that which drives artistic inspiration. I have tried to see this connection in a previous article in The Homeopath, looking particularly at case taking. We would like readers to reflect on these connections and how they may have experienced, used or made art a focus of their homeopathic practice and understanding. I know from starting my group Art and Homeopathy that the direction of our own work is diverse, but all is founded on the principle of using art in some way to clarify and enhance practice. We invite you to then send us in your experience or take on this, be you artist, homeopath or both. This first article tries to set the scene about the inclusivity of art and homeopathy by looking at the breadth of that important quality, expression, as perceived at the outset by Hahnemann, in gaining true insight of the nature of the suffering of the patient.
Keywords: Art; Science; Creativity; Dynamic; Expression; ME; Silica; Pulsatilla; Thuja; Phosphorus